Fotometría de estrellas infrarrojas en cinco micrones - Eugenio, E. (1968)
New observations in 5 μ have been obtained for the infrared stars NML-Tau, TX Cam, BN Mon and T Lyr. The results of this photometry, plus additional measurements in U, B, V, R, T, J, K, L, are given in Tables 1 and 2. The effective temperatures and bolometric corrections for the four objects under study are found in Table 4. We confirm the flat-typed maximum for Carbon Stars. Johnson suggests that it is caused by some absorption within the J-filter. We may conclude that the objects TX Cam and NML-Tau are not Carbon Stars (see Figure 1), most likely, they are M or S long-period variables, because of the light variations and the strong (U-B) - typical of Mira Stars. This is in agreement with our previous results and the spectrophotometric results of Wing, Spinrad and Kuhi.